Fundamentos para uma metafísica de universais imanentes: um esboço de uma teoria de indivíduos como feixes de qualidades espaçotemporais repetíveis - Damo, Homero (2017)
This work aims to study the metaphysics of individuals and how it would be possible to create a metaphysics without the use of them. In this work we first begin with a study on the traditional substrate theory in Locke. Next, we will present Hume’s critique of this model and the idea of our preference for a more parsimonious ontology. Also in this part, we will comment a little bit on the nature and identity of properties. Then, in the second chapter we will present the four versions of the bundle theory. As the name itself says, we will present four interpretations of the bundle metaphor in texts by Van Cleve and Casullo. Each version is presented in it’s main features. The first version of the bundle theory claims that bundles of properties are sets, the second version claims that an individual emerges from the coinstantiation of properties, the third version claims that there is no individuals and the fourth version proposes that there are bundles of bundles. In the third chapter we will deal basically with the problem of the identity of the indiscernibles. We will comment a famous Max Black’s for this purpose. The problem of the identity of the indiscernibles was already mentioned in chapter two, but in this chapter it is worked deeply. In the third chapter we will comment Zimmerman (1997) and O’Leary-Hawthorne (1995) to present the idea of immanent universals. We will try to show how this conception of universals would solve the problem presented by Black. Finally, in the fourth and last part we present Russell’ bundle theory. In this part, the most extensive of this work, we deal, firstly, with the problem of one over many and its relationship with the nature of universals, secondly, with the problem of numerical diversity, thirdly, with the ontology of events, fourtly, with the problem of analyticity, and fifthly the epistemology of the bundles.